Penerapan Arsitektur Neo-Vernacular pada Perancangan Gedung DPRK Bireuen - Ruzwardy, Dedy; Insanuri Qismullah, Fitriyani; Mursal, Muhammad (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The DPRK Bireuen building is a district-level parliamentary building that functions as a place to accommodate activities related to local legislation and budgetin, etc, which is located on the Medan - Banda Aceh Road, Sagoe Village, Peusangan District, Bireuen Regency of Aceh Province - Indoensia. The designed building is expected to be a building that has the identity value of Bireuen Regency while still not only being able to facilitate every parliamentary activity but must also being open to the community aspiration and culture, this is achieved through the application of Neo-vernacular architectural themes in the design. From the results of the analysis conducted, design concepts are obtained that will be applied to the building in the form of cultural elements of Bireuen Regency, both physical and non-physical culture in accordance with Neo-Vernacular architectural methods. Based on this, the DPRK Bireuen building will become a new icon of Bireuen Regency as a reminder of culture and an example for future development in this regency.